Below-Cost Original Equipment Sales as a Promotional Means - Zelenitz, Allan (The Review of Economics and Statistics, 1977)
COMMENCING in 1920, major domestic spark plug manufacturers have sold their original equipment (OE) plugs to the larger automotive vehicle assemblers at a price well below marginal manufacturing cost.' Prior to 1953, when F.T.C. complaints prohibited discriminatory pricing on replacement plugs, the manufacturers gave assemblers lower than wholesale prices on those plugs as well. This discount pricing practice was adhered to whether the sales were interfirm, as, for example, from Autolite to American Motors, or intrafirm, e.g., from General Motor's AC Spark Plug to its car divisions. It has been argued that the below-cost discount price to automobile assemblers is explainable by the existence of an OE-tie, that factory installation of a manufacturer's proprietary brand plug generates profitable replacement sales. Thus, to the extent that spark plugs are replaced with the factory brand, the plug manufacturer realizes a return on his investment in below-cost OE sales. The actual motive force behind the OE-tie is psychologically obscure. It is conceivable that the reason why the OE plug is preferred is that it takes very little effort to know which model to replace, i.e., it is a matter of convenience. But since each of the major plugs is readily available from wholesale distributors and since each manufacturer has a suitable alternative, it is difficult to argue that an appropriate non-OE plug cannot be obtained. Futhermore, it makes little sense to argue, as some have, that the mechanic is wary of customer complaints in case an incorrect plug is installed. Few tune-up customers specify the brand of plug which they wish installed, tending to rely upon the mechanic's superior know-how. Why then do mechanics not use nonOE lesser known or private brands? It could be argued that the service station mechanic, the person who usually chooses the brand, should rationally be indifferent to OE-status and should choose an available cheaper plug, unless he too has been convinced of the importance of OE-status, believing that the replacement plug is the same as that which came with the car when it was new. Recent information indicates that factory authorized dealers sell only about 10% of all replacement plugs, but they are encouraged to use plugs wholesaled to them by their supplying assemblers-the brand supplied being that used by the assembler. Interestingly though, mechanics at these outlets -as well as at automotive service centers operated by firms such as Goodyear, Firestone and Sears, which have or have had their own private branded plugs-also seem to prefer the factory installed OE plug that came with the car. Whatever the reason then, original equipment status appears to be significant in explaining replacement plug sales. Our major contention with regard to brand rivalry within this industry is that having original equipment status should be viewed as an investment, in many ways analogous to expenditures on advertising. Each vehicle maker's spark plug supplier is, by definition, the source of plugs identical in all respects, including brand, to those selected as original equipment by the vehicle manufacturer's engineers. Through its advertising and promotional campaigns, each plug manufacturer stresses that the original equipment plug approved (i.e., purchased) by the vehicle manufacturer is the correct plug to be used for replacement purposes. Once established as Received for publication May 25, 1976. Revision accepted for publication August 30, 1976. *This paper is adapted from my doctoral dissertation (1975). I am deeply indebted to Charles Berry and Stephen Goldfeld of Princeton, Michael Visscher and Dennis Epple of Carnegie-Mellon University, and Jack Ochs of the University of Pittsburgh for their valuable suggestions and criticisms. I Until 1973, an identical price of 5.88a per OE plug was charged by each of the major manufacturers. Since the industry is not subject to substantial scale economies, marginal cost is reasonably approximated by average cost. At no time since World War II has the average cost of manufacture been estimated at less than 1 5a per plug. Information and data used in this article were obtained from the transcripts and exhibits of two District Court trials: U.S. v. Ford Motor Co. et al. (1968 and 1970). I express my gratitude to the Antitrust Division of the U.S. Department of Justice for having granted access to these documents.